2021
DOI: 10.3390/fi13040095
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Applications in Agribusiness: A Systematic Review

Abstract: Blockchain is a technology that can be applied in different sectors to solve various problems. As a complex system, agribusiness presents many possibilities to take advantage of blockchain technology. The main goal of this paper is to identify the purposes for which blockchain has been applied in the agribusiness sector, for which a PRISMA-based systematic review was carried out. The scientific literature corpus was accessed and selected from Elsevier’s Scopus and ISI of Knowledge’s Web of Science (WoS) platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…More specifically, the application of blockchain can help to streamline agrifood chains and tackle several important issues such as the need to reduce food waste [2,3], to increase food chain sustainability [4], and to ultimately improve the quality and healthiness of food products [67]. Furthermore, the bridging techniques and capabilities presented in this paper provide viable managerial policies and strategies which can help to realize the benefits of blockchain that previous research identified for the agroindustry [9]. Our results also provide some indications on how to overcome existing challenges pertaining to the lack of trust and governance, which is an important obstacle in the industry [10].…”
Section: Managerial Contributionsmentioning
confidence: 95%
“…More specifically, the application of blockchain can help to streamline agrifood chains and tackle several important issues such as the need to reduce food waste [2,3], to increase food chain sustainability [4], and to ultimately improve the quality and healthiness of food products [67]. Furthermore, the bridging techniques and capabilities presented in this paper provide viable managerial policies and strategies which can help to realize the benefits of blockchain that previous research identified for the agroindustry [9]. Our results also provide some indications on how to overcome existing challenges pertaining to the lack of trust and governance, which is an important obstacle in the industry [10].…”
Section: Managerial Contributionsmentioning
confidence: 95%
“…Other scholars took olive oil [54], beef [55], coffee [4], and other products as examples to explore consumers' willingness to pay for blockchain traceable products. For example, Williamson [56] studied the willingness of Chinese consumers to pay for mutton certified by the blockchain traceability of the complete supply chain process information from an Australian farm to a restaurant in Shanghai.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sultana, Teoh & Karanasios 2022, Vol 26,Research Article The Impact of Blockchain on Supply Chains been applied in other reviews of IS phenomenon (Frizzo-Barker et al, 2020;Litchfield & Khan, 2019), as well as in blockchain (Chukwu & Garg, 2020;Kuo et al, 2019) and related management reviews (Paliwal et al, 2020;Rocha et al, 2021).…”
Section: Australasian Journal Of Information Systemsmentioning
confidence: 99%